Lanthanide directed self-assembly formations of Tb(iii) and Eu(iii) luminescent complexes from tryptophan based pyridyl amide ligands - GUNNLAUGSSON, THORFINNUR; MCCABE, THOMAS (My University, 2011)
The formation of self-assembly complexes between the ligands 1 (SS) and 2 (RR) and terbium or europium was undertaken and shown (using various spectroscopic titrations) to give rise to the exclusive formation of 2 : 1 (L : Ln) stoichiometry and not the anticipated 3 : 1 stoichiometry.
PUBLISHED
Keywords: stoichiometry; Tb(III); Eu(III); luminescent complexes; tryptophan based; ligands; Nanoscience & Materials